PENCIPTAAN FILM DOKUMENTER “KEMBANG JENAR” DENGAN GAYA EKSPOSITORI - Widnyana, I Kadek Wira; Puriartha, I Kadek; Yasa, Desak Putu Yogi Antari Tirta (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
ndependent Project Activities are part of the Merdeka Belajar Kampus Merdeka (MBKM) program, designed to provide students with opportunities to create innovative works either independently or in interdisciplinary groups. This program aims to complement the formal curriculum with topics not covered in regular courses. Independent Projects facilitate collaboration between students and external partners to produce creative works with a wide-reaching impact. As part of this program, the author will produce a documentary film titled Kembang Jenar, which highlights the traditional Baris Kembar dance. The documentary, created in an expository style, focuses on presenting facts, events, people, and places associated with Baris Kembar dance. The film narrates the story of the pengadeg sesuunan Baris Kembar, individuals chosen from childhood to shoulder the responsibility of preserving this tradition.